The mediating roles of physical exercise and social-psychological stress in the relationship between socioeconomic status and self-rated health - Xiaosheng Lei; Song He; Heng Jiang; Aijun Xu (PLoS ONE, 2026)
Objectives Although the relationship between socioeconomic status (SES) and health is well documented, the contributions of physical exercise (PE) and social-psychological stress (SPS) to this association remain insufficiently understood. This study aimed to explore the mediating roles of PE and SPS in the relationship between SES and self-rated health (SRH). Methods This study included 1,507 participants (aged ≥ 16 years) from the Health Survey conducted in Hubei Province during the post-pandemic period of 2021. Structural equation modeling (SEM) was used to examine the mediating and interaction effects, with PE and SPS specified as mediators in the association between SES and SRH. Results The average SES and SRH scores were 3.07 ± 1.12 and 2.93 ± 0.93, respectively. Significant pairwise correlations ( p < 0.05) were found among SES, PE, SPS and SRH. Low SES was associated with poorer SRH (β = 0.23), as were insufficient PE (β = 0.11) and higher SPS (β = –0.17). Both PE and SPS demonstrated significant mediating effects, accounting for 6.7% and 14.2% of the total impact of SES on SRH, respectively. The interaction between PE and SPS was statistically significant only among females ( p < 0.05). Conclusions This study confirms that physical exercise and social-psychological stress play partial mediating roles in the association between SES and SRH. The findings suggest that limited physical exercise and higher levels of social-psychological stress may adversely affect health, particularly with low SES. Promoting healthy lifestyles and supportive social environments is therefore crucial for improving population health.